STUDI DESKRIPTIF TENTANG KOMUNIKASI INTERPERSONAL DAN CHARACTER STRENGTHS REMAJA KORBAN BULLYING - Junaidin; Erliana, Yossy Dwi; Mustafa, Kartika; Hartono, Roni; Yuliarti (KAGANGA KOMUNIKA: Journal of Communication Science, 2025)
Bullying remains a serious problem in adolescent development, particularly due to its widespread impact on psychological, social, and emotional aspects. Adolescents who experience bullying tend to face obstacles in forming social relationships, including a decline in interpersonal communication skills that play an important role in daily interactions. This study uses a descriptive approach with the aim of identifying patterns of interpersonal communication and aspects of character strengths that emerge in adolescents who have experienced bullying. Data were collected through interviews, observations, and relevant measurement instruments to gain an in-depth understanding of the psychological condition of the subjects. The subjects in this study were three adolescents who were victims of bullying. The results of the study show that adolescent victims of bullying generally tend to withdraw from social interactions, experience barriers in expressing their thoughts, stress, anxiety, lack of motivation to study, and emotions, and exhibit low self-confidence in communication. In terms of character strengths, it was found that some character strengths such as courage, perseverance, and emotional regulation had declined, although some aspects such as empathy and gratitude were still evident in some subjects.   Keywords: Interpersonal Communication, Character Strengths, Bullying